Heterogeneity of the Transmembrane Protein Conformation in Purple Membranes Identified by Infrared Nanospectroscopy. Issue 44 (27th September 2017) - Giliberti, Valeria; Badioli, Michela; Nucara, Alessandro; Calvani, Paolo; Ritter, Eglof; Puskar, Ljiljana; Aziz, Emad Flear; Hegemann, Peter; Schade, Ulrich; Ortolani, Michele; Baldassarre, Leonetta
Abstract: Cell membranes are intrinsically heterogeneous, as the local protein and lipid distribution is critical to physiological processes. Even in template systems embedding a single protein type, like purple membranes, there can be a different local response to external stimuli or environmental factors, resulting in heterogeneous conformational changes. Despite the dramatic advances of microspectroscopy techniques, the identification of the conformation heterogeneity is still a challenging task. Tip‐enhanced infrared nanospectroscopy is here used to identify conformational changes connected to the hydration state of the transmembrane proteins contained in a 50 nm diameter cell membrane area, without the need for fluorescent labels. In dried purple membrane monolayers, areas with fully hydrated proteins are found among large numbers of molecules with randomly distributed hydration states. Infrared nanospectroscopy results are compared to the spectra obtained with diffraction‐limited infrared techniques based on the use of synchrotron radiation, in which the diffraction limit still prevents the observation of nanoscale heterogeneity. Abstract : Cell membranes are intrinsically heterogeneous, as the local protein and lipid distribution is critical to physiological processes. Tip‐enhanced infrared nanospectroscopy enables an unprecedented small number of molecules in the mid‐infrared to be probed, on a deepsubwavelength scale. Infrared nanospectroscopy can identify heterogeneous conformational changes connected to hydration of transmembrane proteins contained in membrane monolayers.